1998
DOI: 10.1073/pnas.95.7.3402
|View full text |Cite
|
Sign up to set email alerts
|

A single side chain prevents Escherichia coli DNA polymerase I (Klenow fragment) from incorporating ribonucleotides

Abstract: Although nucleic acid polymerases from different families show striking similarities in structure, they maintain stringent specificity for the sugar structure of the incoming nucleoside triphosphate. The Klenow fragment of E. coli DNA polymerase I selects its natural substrates, deoxynucleotides, over ribonucleotides by several thousand fold. Analysis of mutant Klenow fragment derivatives indicates that discrimination is provided by the Glu-710 side chain which sterically blocks the 2-OH of an incoming rNTP. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
209
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(228 citation statements)
references
References 35 publications
13
209
0
1
Order By: Relevance
“…3). Similar pausing sites were also observed with other DNA polymerase mutants that acquired RNA polymerase activities [9,12,18,19]. One possible explanation is that for the enzyme to accommodate the RNA products containing 2-7 rNTPs, the active site is changed to a position that is not suitable for efficient catalysis.…”
Section: Discussionsupporting
confidence: 70%
“…3). Similar pausing sites were also observed with other DNA polymerase mutants that acquired RNA polymerase activities [9,12,18,19]. One possible explanation is that for the enzyme to accommodate the RNA products containing 2-7 rNTPs, the active site is changed to a position that is not suitable for efficient catalysis.…”
Section: Discussionsupporting
confidence: 70%
“…RB69 DNA polymerase also shows effects in both K D and k pol , achieving an even higher discrimination by virtue of a 230-fold weaker ground state binding. Discrimination against NTPs has, in large part, been attributed to a steric clash between the 2Ј-OH and a conserved side chain in the polymerase active site (26,30,32 b The kinetic parameters for Vent A488L DNA polymerase are from single determinations.…”
Section: ͻ10mentioning
confidence: 99%
“…In the case of Family A DNA polymerases from bacteriophage T7, Escherichia coli (Klenow fragment, large fragment of DNA polymerase I), and Thermus aquaticus, as well as the Family B DNA polymerase from bacteriophage RB69, interpretation of the structural information is complemented by steady-state and pre-steady-state kinetic studies, allowing a detailed description of the polymerization pathway. Reaction parameters describing the discrimination against naturally occurring nucleotide analogs encountered in vivo, such as NTPs, or unnatural nucleotide analogs, such as ddNTPs and dyelabeled ddNTPs (13,(25)(26)(27)(28)(29)(30), have added insights into the basis for nucleotide discrimination.Hyperthermophilic archaeal DNA polymerases have not been scrutinized in such detail, hampering a complete characterization and comparison with other polymerases. Family B DNA polymerases from hyperthermophilic Archaea Thermococcus sp.…”
mentioning
confidence: 99%
“…Early studies (reviewed in (1,2)) revealed that DNA polymerases do incorporate rNMPs during DNA synthesis. Kinetic studies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) have further demonstrated that selectivity for insertion of dNMPs into DNA rather than rNMPs varies from 10-fold to >10 6 -fold, depending on the DNA polymerase and the dNTP/rNTP pair examined. rNMP incorporation during DNA synthesis is potentially made more probable by the fact that the concentrations of rNTPs in vivo are higher than are the concentrations of dNTPs (e.g., see refs.…”
mentioning
confidence: 99%